FROM INVESTORS TO DO-IT-ALL: CHINESE IMMIGRANTS, THEIR ACTIVITIES AND LOCAL PEOPLE’S PERCEPTIONS IN TANZANIA, 1990s TO PRESENT - (:unkn) unknown (My University, 2022)
Since the 1990s, there has been an unprecedented rise in the number of Chinese immigrants across Africa. In Tanzania, the influx of Chinese people forming social-economic clusters—‘Chinatowns’ is springing. The new individual Chinese quest for achievement, necessitating new waves of migration to Africa, is not yet well researched. This paper examines this new trend as it manifests in the Tanzanian context. It looks at the motivation for Chinese migration to Tanzania, their networks, activities, and the local people’s perceptions of those engagements. Using information gathered from surveys, written and oral sources, the paper establishes that since the 1990s, Chinese migrants have increasingly turned from investors to engage in almost every small business they come across. Because of Tanzania’s generally small local economies, these relatively new entrants to a market have undoubtedly caused mixed perceptions among the locals. While the Sino-African relationship is generally viewed positively by the Tanzanians, the Chinese residing in the country are perceived less positively, as exemplified by perceived hostility and rudeness from the Chinese migrants.
Keywords: African Research